The Cambridge handbook of corporate law, corporate governance and sustainability / edited by Beate Sjåfjell, Christopher M. Bruner. - Sjåfjell, Beate; Bruner, Christopher M., 1972- (Cambridge University Press, 2020)
The emerging field of corporate law, corporate governance and sustainability is one of the most dynamic and significant areas of law and policy in light of the convergence of environmental, social and economic crises that we face as a global society. Understanding the impact of the corporation on society and realizing its potential for contributing to sustainability is vital for the future of humanity. This Handbook comprehensively assesses the state-of-the-art in this field through in-depth discussion of sustainability-related problems, numerous case studies on regulatory responses implemented by jurisdictions around the world, and analyses of predominant strategies and potential drivers of change. This Handbook will be an essential reference for scholars, students, practitioners, policymakers, and general readers interested in how corporate law and governance have exacerbated global society's most pressing challenges, and how reforms to these fields can help us resolve those challenges and achieve sustainability.